2018
DOI: 10.1093/cvr/cvy200
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor-gamma targeting nanomedicine promotes cardiac healing after acute myocardial infarction by skewing monocyte/macrophage polarization in preclinical animal models

Abstract: Nanoparticle-mediated targeting of pioglitazone to inflammatory monocytes protected the heart from IR injury and cardiac remodeling by antagonizing monocyte/macrophage-mediated acute inflammation and promoting cardiac healing after AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 45 publications
0
53
0
Order By: Relevance
“…Lee and colleagues found that YAP/TAZ participates in the regulation of 135 genes in macrophages, of which 66 were closely related to cell development, differentiation, metabolism, and immunity, including PPARg, myoblast determination protein (MyoD), the zinc finger of the cerebellum 1 (Zic1), and lymphocyte function-associated antigen 1 (LF-A1) (87). The transcription factor PPARg has also been reported to modulate the polarization and inflammatory responses of macrophages (42,43,93). YAP/TAZ plays a crucial role in the biological activity of macrophages.…”
Section: Yap/taz In Regulating Macrophagesmentioning
confidence: 99%
“…Lee and colleagues found that YAP/TAZ participates in the regulation of 135 genes in macrophages, of which 66 were closely related to cell development, differentiation, metabolism, and immunity, including PPARg, myoblast determination protein (MyoD), the zinc finger of the cerebellum 1 (Zic1), and lymphocyte function-associated antigen 1 (LF-A1) (87). The transcription factor PPARg has also been reported to modulate the polarization and inflammatory responses of macrophages (42,43,93). YAP/TAZ plays a crucial role in the biological activity of macrophages.…”
Section: Yap/taz In Regulating Macrophagesmentioning
confidence: 99%
“…Peripheral monocytes/macrophages and cardiac‐resident macrophages migrate to the infarct and border region, differentiate into M1 macrophages, and exacerbate cardiac function. Thereafter, entering the inflammation resolution stage, the dominant macrophage populations of myocardial tissues become reparative M2 macrophages that accelerate cardiac repair (Gombozhapova et al, ; Tokutome et al, ). Inflammation from M1 macrophages is an essential component of early ventricle remodeling, and prolonged inflammation may damage the physiology of the left ventricle (LV) by raising LV expansion and redundant scar transformation (Ben‐Mordechai et al, ; Gombozhapova et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…[140] PPAR activation in monocytes/macrophages, obtained by targeting a PPAR agonist to phagocytes with a nanocarrier, achieved promising results in a preclinical model of myocardial infarction. [141] Modulation of PPAR activity via NM may therefore be developed as a novel therapeutic strategy for anti-inflammatory and pro-healing effects.…”
Section: Nanomaterials and Activation Of Innate Immune Genes/factorsmentioning
confidence: 99%